Vitamin D as a Risk Factor for Multiple Sclerosis: Immunoregulatory or Neuroprotective? - Gombash, Sara E.; Lee, Priscilla W.; Sawdai, Elizabeth; Lovett-Racke, Amy E. (Frontiers in Neurology, 2022)
Vitamin D insufficiency during childhood has been linked to the development of multiple sclerosis (MS), typically an adult-onset inflammatory demyelinating disease of the central nervous system (CNS). Since vitamin D was known to have immunoregulatory properties on both innate and adaptive immunity, it was hypothesized that low vitamin D resulted in aberrant immune responses and the development of MS. However, vitamin D receptors are present on many cell types, including neurons, oligodendrocytes, astrocytes and microglia, and vitamin D has profound effects on development and function of the CNS. This leads to the possibility that low vitamin D may alter the CNS in a manner that makes it vulnerable to inflammation and the development of MS. This review analysis the role of vitamin D in the immune and nervous system, and how vitamin D insufficiency in children may contribute to the development of MS.